(untitled) (Journal of Oriental Studies, 2024)
The significance and role of the basic conditions for the economic miracle of China and the formation of China as a world hegemon and leader are characterized. Answers are given to directly posed questions of how and why China has obtained not only positive, but phenomenal development results in such a short time. How China managed to virtually eradicate poverty and feed its 1.5 billion people. Initially, the strategic goals, model and mechanisms for achieving the economic development of the leading countries of the world by attracting their capital and technology were correctly set. Economic modernization contained the export orientation of the economy, the attraction of foreign investment and technology, a high share of investment in GDP, and the active participation of the state in the development of the economy. The direct leadership of the modernization of the economy was carried out by the Communist Party of China. The conditions that determined the success of the developed economic model of modernization include effective factors: a huge labor market, imports of ethnic Chinese foreign capital. Drivers of growth and experimental platforms for market reforms were special economic zones opened under the developed Program. The visible success of special economic zones led to the creation of a network of territories "Zones of Economic and Technological Development". The privatization of state-owned enterprises has Chinese specifics: Chinese privatization does not mean the state’s withdrawal from economic activity. In all strategic areas of China, the monopoly of state-owned enterprises has been preserved. The engine of growth is large (including those occupying a monopoly position) state-owned corporations seeking to invest their profits in new projects. China in the 21st century is transforming the economy into a new technological and innovative level. Key words: China, model, economic miracle, growth rates, strategy, modernization.